2007
DOI: 10.3748/wjg.v13.i3.383
|View full text |Cite
|
Sign up to set email alerts
|

A specific gene-expression signature quantifies the degree of hepatic fibrosis in patients with chronic liver disease

Abstract: AIM:To study a more accurate quantification of hepatic fibrosis which would provide clinically useful information for monitoring the progression of chronic liver disease. METHODS:Using a cDNA microarray containing over 22 000 clones, we analyzed the gene-expression profiles of non-cancerous liver in 74 patients who underwent hepatic resection. We calculated the ratio of azanstained: total area, and determined the morphologic fibrosis index (MFI), as a mean of 9 section-images. We used the MFI as a reference st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In our own analysis of the liver microarray data, we observed similar trends of gene expression changes as the Utsunomiya group and confirm the importance of inflammatory genes in that dataset (not shown). We found that most MARGS were in fact underrepresented in the fibrosis group (not shown), while proinflammatory genes were largely overrepresented and correlated with the adjusted MFI fibrosis grade, as published [9]. Recently, the group of Takahara has shown in gene expression studies of fibrosis in HCV patients that ECM modulatory genes in general positively correlate with the METAVIR F-score 1 through 4, and some genes had peak expression changes in fibrosis score 2 and 3 [28].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In our own analysis of the liver microarray data, we observed similar trends of gene expression changes as the Utsunomiya group and confirm the importance of inflammatory genes in that dataset (not shown). We found that most MARGS were in fact underrepresented in the fibrosis group (not shown), while proinflammatory genes were largely overrepresented and correlated with the adjusted MFI fibrosis grade, as published [9]. Recently, the group of Takahara has shown in gene expression studies of fibrosis in HCV patients that ECM modulatory genes in general positively correlate with the METAVIR F-score 1 through 4, and some genes had peak expression changes in fibrosis score 2 and 3 [28].…”
Section: Discussionsupporting
confidence: 72%
“…Gene expression datasets for heart and lung were downloaded from Gene Expression Omnibus, http://www.ncbi.nlm.nih.gov/geo, Heart: GSE5406 [7], Lung: GSE10667 [1]. Liver and pancreas data were provided by the authors [9,10].…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular characteristics of hepatic fibrosis have been examined during the progression [26], and a number of differentially expressed genes, such as Tmsb10, emp1, Cd24, and Lgals3, possibly associated with hepatocarcinogenesis were identified [27,28]. Therefore, it is plausible to expect that a specific molecular signature in the noncancerous liver tissue specimens might predict a risk of multicentric occurrence of HCC or late recurrence after surgery [20].…”
Section: Molecular Prediction Of Late Recurrence Of Hcc Using Nontumomentioning
confidence: 99%